A comparison to methyl bromide with two alternatives treatments; sulfuryl fluoride and heat to control stored products insects - Muhareb, Jeannette S. (Kansas State University, 2010)
Environmental concerns are growing as new information is being discovered as to what is harmful to the environment. The desire to help the environment along with improving fumigations is a big concern and effects many people. Ongoing research to improve fumigations without harming the environment has shown great promise in advancing technology and lowering the cost in protecting commodities consumed by the consumer. Methyl Bromide (MB) has been the major fumigant used to control stored-product insects for many commodities for many years. There has been a lot of concern surrounding MB because of health and environmental drawbacks. These concerns have caused MB to be reduced by 2005. With the total phase out of MB becoming critical, there is much anticipation as what will be the alternative(s). The research presented in this thesis describes two different and very effective methods of controlling stored product insects. Although there are many other methods of fumigating this thesis analyzes two forms; Sulfuryl Fluoride and Heat. The first presented alternative in this paper will be heat treatments. It has the attraction that chemical forms of treatments do not have by having pesticide-free products. The total cost of heat fumigation depends on the complexity of the lay-out/structure and the cost heaters and electricity. This cost can range anywhere from $15,000-25,000. The second alternative that will be discussed is sulfuryl fluoride. This fumigant has many positive aspects that counter act the negative aspects that have been a concern with methyl bromide treatments. These positive aspects include environmentally safe and fast off-gassing. Sulfuryl fluoride is also very efficacious with stored product insects. The labor costs per job, ProFume shows a cost of about $216.00 less than that of a methyl bromide treatment.
Keywords: Methyl Bromide; ProFume; Heat Treatment; Cost; Effectiveness; Food-Processing Facilities; Agriculture, General (0473); Biology, General (0306); Economics, General (0501)